Redes sociais dialógicas no contexto da avaliação aberta - Silva, Kleisson Lainnon Nascimento da (2023)
The relationships that involve authors and referees in the scope of blind evaluation attribute to the editor the responsibility of intermediating the exchange of messages, making it impossible to consolidate the scientific practice in a bidirectional perspective. The parity review that is based on the philosophy of Open Science evokes the configuration of networks, with dialogue as a driving force for the establishment of connections between the individuals who perform it and, in certain circumstances, dispensing with editorial mediation. The notion of dialogical networks in the context of open peer review provides the opportunity to design bimodal arrangements, composed of actors who simultaneously assume multiple positions – authors, evaluators and editors – in the field of Scientific Communication. The study analyzes the dialogical social network of the open evaluation process of articles located in the Communication and Media area, published by F1000Research from 2012 to 2021. Methodologically, the research is configured as descriptive, documental, based on the quantitative and qualitative bias. The weighting of the data was governed by the analysis of social networks and the analysis of the dialogues took place through content analysis. The macro structure consists of 200 actors, 136 (70%) are evaluators and 61 (28%) are corresponding authors and only three (2%) simultaneously perform such functions. They are distributed in 56 subnets, making up 22 triads, 19 tetrads, 10 pentades, four hexades and a dyad. The researchers ILLLINGWORTH, S., SILALAHI, W. P., TENNANT, J., PROKOP, A., MARINKOVIC, M., EVANS, T. M., GRAY, J. and BLOCK, T. J., FORD, E., ROSS-HELLAUER, T. stand out with a degree of centrality. Regarding the nature of the links, they are characterized by interinstitutional (84%) and hybrid (16%) relations between teaching and research institutions of an international nature, located predominantly in the countries of North America and Europe. The dialogues from the opinions were grouped into six categories – adjustment of the pre-textual items, outlines of the introductory elements, theoretical framework, methodology, final considerations and research data – referring to the theme of the messages they shared throughout the evaluation. The results of the research allow us to conclude that the dialogue and its consequences allied to the parity evaluation in the editorial context make the process dynamic, since referees and correspondents assume the position of collaborators, favoring the discussion of aspects that can be incorporated or excluded from the manuscript. It is reinforced that through the network of dialogues, in most cases, the actors reflect and position themselves constructively on the suggestions and with a view to repairing existing weaknesses in the thematic and physical framework of the publication, adapting them to the scope of the journal.